2016
DOI: 10.1093/pm/pnw133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Common Single Nucleotide Polymorphisms in Complex Regional Pain Syndrome: Genome Wide Association Study Approach and Pooled DNA Strategy

Abstract: Despite the fact that we interrogated about 83% of all of common SNPs in the human genome, we did not find evidence that any of the investigated common SNPs may be associated with CRPS phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…By contrast, in another study, no differences in DNA single­nucleotide polymorphisms (SNPs) were found between patients with CRPS and unspecified controls 63 . A large number of SNPs (>200,000) were analysed, but no difference passed the statistical threshold after Bonferroni correction.…”
Section: Diagnostic Features and Biomarkersmentioning
confidence: 85%
“…By contrast, in another study, no differences in DNA single­nucleotide polymorphisms (SNPs) were found between patients with CRPS and unspecified controls 63 . A large number of SNPs (>200,000) were analysed, but no difference passed the statistical threshold after Bonferroni correction.…”
Section: Diagnostic Features and Biomarkersmentioning
confidence: 85%
“…A conflicting study in 2016 looked at >200 000 single nucleotide polymorphisms between CRPS patients and control groups, and found no significant difference in expression between the two. 30 More investigation is needed to determine if there is a genetic link to developing CRPS.…”
Section: Genetic Influencementioning
confidence: 99%
“… 74 Associations with known gene polymorphisms have been described in smaller studies but could not be replicated in larger cohorts. 44 As long as we do not have biomarkers for subgrouping, the detection of genetic factors will remain difficult. Furthermore, association studies need high numbers, but CRPS is a rare disease.…”
Section: Pathophysiology Of Complex Regional Pain Syndromementioning
confidence: 99%